Intracerebral hemorrhage-induced brain injury in rats: the role of extracellular peroxiredoxin 2 - Bian, Liheng (Transl Stroke Res, 2019)
Red blood cell (RBC) lysis within the hematoma causes brain injury following intracerebral hemorrhage. Peroxiredoxin 2 (PRX-2) is the 3rd most abundant protein in RBCs and this study examined the potential role of PRX-2 in inducing brain injury in rats. First, adult male Sprague-Dawley rats had an intracaudate injection of lysed RBCs or saline. Brains were harvested at one hour to measure PRX-2 levels. Second, rats had an intracaudate injection of either recombinant PRX-2, heat-inactivated PRX-2 or saline. Third, rats had intracaudate coinjection of lysed RBCs with conoidin A, a PRX-2 inhibitor, or vehicle. For the second and third parts of studies, behavioral tests were performed and all rats had magnetic resonance imaging prior to euthanasia for brain immunohistochemistry and Western blotting. We found that brain PRX-2 levels were increased after lysed RBC injection. Intracaudate injection of PRX-2 resulted in blood-brain barrier disruption, brain swelling, neutrophils infiltration, microglia activation, neuronal death, and neurological deficits. Intracerebral injection of lysed RBCs induced brain injury, which was reduced by conoidin A. These results suggest that extracellular PRX-2 released from hematoma can cause brain injury following brain hemorrhage and could be a potential therapeutic target.